DOI: 10.11606/t.44.1995.tde-11062015-094515
|View full text |Cite
|
Sign up to set email alerts
|

Depósitos cenozoicos costeiros e a morfologia do extremo sul de Santa Catarina

Abstract: Âliuro Mddio : 652,90m Cocf Moslividod!: O,712 (d .35'27'ì6") coel. orogrólico 464,86 too% Areo : I O l,l7 km2 a[uro Mddìo : 7ì6,67m

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
15

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 11 publications
0
5
0
15
Order By: Relevance
“…Such interpretation is supported by the similarity between characteristics of alluvial surface coverings arranged on the low fl uvial and fl uvial-marine terraces and the materials from the plateau edge and from alluvium-colluvial deposits of alluvial fans at the base of the upstream escarpment until near the ocean plain, where they dive underneath the marine sediments from the Upper Pleistocene and Holocene, detailed by Duarte (1995), Pontelli and Pellerin (1998), Krebs (2004), Dantas et al (2005), Pontelli (2005), andHorn Filho et al (2014).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Such interpretation is supported by the similarity between characteristics of alluvial surface coverings arranged on the low fl uvial and fl uvial-marine terraces and the materials from the plateau edge and from alluvium-colluvial deposits of alluvial fans at the base of the upstream escarpment until near the ocean plain, where they dive underneath the marine sediments from the Upper Pleistocene and Holocene, detailed by Duarte (1995), Pontelli and Pellerin (1998), Krebs (2004), Dantas et al (2005), Pontelli (2005), andHorn Filho et al (2014).…”
Section: Discussionmentioning
confidence: 84%
“…Radiocarbon (C 14 ) dating results in shell-mounds and palynological records carried out by Duarte (1995), Cancelli (2012), and Schneider (2012) suggest progressive continuation of this marine regression, with moments of stabilization over the years, revealing more recent ages in this geomorphological surface (GS-III) to the extent that areas closer to the current shoreline were dated (4.150 ± 20 / 3.550 ± 30 / 1.740 ± 25 years B.P.). The dating carried out by this research in the bottom edge of this marine terrace showed age of 210 ± 25 years B.P., a result that confi rms and reinforces such interpretations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ao Leste encontram-se planícies compostas por praias arenosas e um complexo lagunar de formação geológica muito recente, marcada pela cobertura sedimentar quaternária (Duarte, 1995). Ao centro, encontram-se terrenos sedimentares mais antigos (Paleozóico), composto de arenitos, argilitos e siltitos, cujas formas colinosas decorrem de intenso processo de desgaste.…”
Section: Introductionunclassified